Renal involvement in leptospirosis: new insights into pathophysiology and treatment - Thaís Bandeira Cerqueira (Brazilian Journal of Infectious Diseases)
Acute renal failure (ARF) is one of the most common complications of leptospirosis although the causal mechanisms are still unclear. Diverse mechanisms are implicated in leptospiral nephropathy and new data supports the role of peculiar ion transport defects. Besides antibiotic therapy, ARF management in leptospirosis requires dialytic therapy which is most efficient when started early. Dialysis is the standard supportive therapy even though recent evidence suggests clinical benefit from alternative treatments such as plasmapheresis and hemofiltration. Renal recovery is achieved soon after clinical improvement. The comprehension of the primary mechanisms of renal dysfunction will be helpful in the development of additional therapeutic tools for improving supportive therapy for leptospiral nephropathy. This review discusses new insights into mechanisms implicated in leptospiral ARF and recent advances in treatment.